Studi Kasus : Asuhan Keperawatan TN. A dengan Intervensi Terapi Rileksasi Benson dalam Menurunkan Kadar Gula Darah pada Pasien Diabetes Melitus di RSUD dr. T. C. Hillers Maumere - Rosa Myastica M.J Nurak; Anggia Riske Wijayanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Diabetes Mellitus is a serious chronic disease that occurs when the pancreas does not produce enough insulin (a hormone that regulates blood sugar or glucose), or when the body cannot effectively use the insulin it produces. According to the American Diabetes Association (ADA) in 2010, Diabetes Mellitus (DM) is a group of metabolic diseases with characteristic hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both. This study aims to apply the Benson relaxation therapy intervention to reduce blood sugar levels. The type/research design used is descriptive method with a case study approach, sample 1 client. The approach used is the nursing care approach which includes the identification of data from the results of the assessment, nursing diagnosis, planning, implementation and evaluation. Benson relaxation therapy was carried out for 3 days. Data collection techniques used the medical surgical nursing care assessment format, observation and literature study. The results of this study show that case studies show patients with DM who have nursing problems of blood glucose instability who have a main complaint of weak body, frequent urination at night, often dry and cold and the results of laboratory tests found an increase in blood sugar levels. The conclusion from the results of this case study research is that in nursing care for DM patients the main problem that must be resolved is to lower blood sugar levels.